Nasr Hamid Abu Zayd's interpretation of the Qur'an on women's rights : a critical evaluation - Rakhman, Ali (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
The study investigated Nasr Hamid Abu Zayd's Qur'anic interpretation on women's rights in Islam, particularly on three crucial issues, namely awrah and hijab, polygamy, and leadership of men over women. Those interpretations were examined critically alongside classical and contemporary Muslims scholars' interpretations. The study was conducted using library research by collecting primary and secondary sources to obtain the necessary information and required data. The findings indicated that Abu Zayd rejected the authority of classical method in interpreting the Qur'an. He considered that the Qur'anic interpretations related to women's rights were influenced by patriarchal Arab culture and were dominated by men through gender bias with the purpose to humiliate women and place them in the lower social status. His interpretation of Qur'an on women's rights in Islam was influenced by western views that attempted intensively to place men and women equally in all aspects of life.